2016
DOI: 10.1111/mmi.13385
|View full text |Cite
|
Sign up to set email alerts
|

Direct sensing and signal transduction during bacterial chemotaxis toward aromatic compounds in Comamonas testosteroni

Abstract: Micro-organisms sense and chemotactically respond to aromatic compounds. Although the existence of chemoreceptors that bind to aromatic attractants and subsequently trigger chemotaxis have long been speculated, such a chemoreceptor has not been demonstrated. In this report, we demonstrated that the chemoreceptor MCP2901 from Comamonas testosteroni CNB-1 binds to aromatic compounds and initiates downstream chemotactic signaling in addition to its ability to trigger chemotaxis via citrate binding. The function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 67 publications
(107 reference statements)
0
29
0
Order By: Relevance
“…All of these compounds support the growth of the bacterium (Ni et al, 2013b) and further studies showed that the chemoreceptors MCP2201, MCP2901, and MCP2983 mediate taxis to these compounds (Ni et al, 2013a, 2015; Huang et al, 2016). These receptors possess a four-helix bundle LBD but employ different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these compounds support the growth of the bacterium (Ni et al, 2013b) and further studies showed that the chemoreceptors MCP2201, MCP2901, and MCP2983 mediate taxis to these compounds (Ni et al, 2013a, 2015; Huang et al, 2016). These receptors possess a four-helix bundle LBD but employ different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was supported by the fact that the observed chemotaxis was metabolism dependent (Ni et al, 2013a). In marked contrast, the mechanism of MCP2901 is based on the direct binding of aromatic acids to the periplasmic LBD (Huang et al, 2016); although affinities were relatively weak ( K D values typically of several hundreds of μM) and thus inferior to the corresponding values of PcaY_PP. Taken together, there are thus two fundamentally different mechanism of chemotaxis to aromatic acids.…”
Section: Discussionmentioning
confidence: 99%
“…The MCP2201 gene, as well as its upstream 150 bp DNA that contains a native promoter, has been inserted into the plasmid pBBR1MCS-2 for chemotaxis assays. This plasmid has been used in the study of another C. testosteroni chemoreceptor MCP2901 (Huang et al, 2016) and its copy number is 6 per cell in C. testosteroni (Xiong and Maser, 2001). Swimming plate assays were performed as previously described (Huang et al, 2016).…”
Section: Strains Cultural Conditions and Chemotaxis Assaysmentioning
confidence: 99%
“…Halogenated aromatic compounds are found in many industrial commodities such as pesticides, flame-retardants, hydraulic fluids, and synthetic intermediates for pharmaceutical agents [24]. Several strategies are being explored to remove these toxic compounds from the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies are being explored to remove these toxic compounds from the environment. One particularly attractive strategy is bioremediation, which uses microbial catabolic pathways to process the toxic species to metabolic intermediates that frequently can be channeled to the Krebs Cycle [25]. This approach requires a thorough understanding of each of the pathway steps.…”
Section: Introductionmentioning
confidence: 99%